the EFFECTIVENESS OF TRAINING AND ASSISTANCE TO IMPROVE TEACHERS' ABILITY IN CLASS MANAGEMENT TOWARDS QUALITY PAUD - nureda nureda; Lilis Suryani; Arini Susanti; Enny Purwanti; Maria Marlena Naif (Universitas Panca Sakti Bekasi, 2023)
RA is an educational institution for young children in the Cikarang Timur sub-district, Bekasi district, with a total of 17 institutions with 44 people, approximately 90% of whom still use classical learning models and utilize student worksheets in the learning process. From this, the idea emerged to provide training and assistance to teachers. -teacher Ra to increase teacher competence in management, especially in implementing a learning-centred model. This study used descriptive qualitative methods with data collection techniques through observation of activities using observation instrument guidelines and interviews with teachers using instrument guidelines and documentation. This research was carried out on March 11, 2023, to March 17, 2023, with details of one day of activities used for training and 5 days used for mentoring. in training and mentoring activities for 44 teachers for 17 institutions in RA Cikarang Timur Bekasi district, the results obtained from this study indicate that training And mentoring are very effective in increasing teachers' abilities in classroom management to create meaningful and enjoyable learning to create quality early childhood education.